The Role of Social Media and Social Influence on Firm Performance: Case Study of Financial Industry in Indonesia - Abdillah, Pujangga (University of Merdeka Malang, 2022)
The purpose of this research is to verify the impact of social media and social influence on firm performance in Indonesia’s financial industry. Samples were taken using the judgment sampling technique with a total sample of 126 observations. This research utilizes content analysis, fixed-effects, and random-effects models to verify the effect of engaging in social media and social influence on firm performance. The empirical study consists of panel data in the financial industry listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2021. All secondary data is analyzed by moderated regression analysis (MRA) with STATA program. The results explained that social media has an impact on firm performance as estimated by return on asset (ROA). That is, a higher social media made firm can improve firm performance. The study result also suggests that social influence estimates have the pressure to predict firm performance.